Psychiatrists as Gatekeepers of War Expenditure: Diagnosis and Distribution of Military Pensions in Japan during the Asia-Pacific War. Issue 1 (1st March 2019) - Nakamura, Eri
Abstract: Similar to other modern Western nations, Japan experienced a state of total war during the twentieth century, expanding state intervention in the economy, scientific community, and the bodies of the populace. This article illustrates how Japanese psychiatrists engaged in the production of knowledge and the distribution of government funds via war disablement pensions in response to national demands during the Asia-Pacific War (1931–45). After the Second Sino-Japanese War started in July 1937, Kōnodai Military Hospital was converted into a special army hospital for mental and neurological illnesses, admitting about 10, 500 patients by the end of the war. Most of the psychiatrists assigned to Kōnodai Military Hospital were elite professionals who went on to be leaders in Japanese psychiatry after the war. It is noteworthy that the main task of these psychiatrists was not only to treat patients but also to make judgments on who would or would not receive war disablement pensions. Their interpretation of what was termed "war neurosis" became closely aligned with the goals of the war disablement pension system and was affected by economic needs during and after the war. This article reveals that wartime economic decision making by the government demanded medical officers to make it clear who deserved a war disablement pension in order to minimize potentially excessive spending on "pension neurosis."